Safety and Efficacy of Combined Intramuscular/Intranasal RAZI-COV PARS Vaccine Candidate Against SARS-CoV-2: A Preclinical Study in Several Animal Models - Banihashemi, Seyed Reza; Es-haghi, Ali; Fallah Mehrabadi, Mohammad Hossein; Nofeli, Mojtaba; Mokarram, Ali Rezaei; Ranjbar, Alireza; Salman, Mo; Hajimoradi, Monireh; Razaz, Seyad Hossein; Taghdiri, Maryam; Bagheri, Mohsen; Dadar, Maryam; et al. (Frontiers in Immunology, 2022)
Several vaccine candidates for COVID-19 have been developed, and few vaccines received emergency approval with an acceptable level of efficacy and safety. We herein report the development of a first recombinant protein-based vaccine in Iran based on the recombinant SARS-CoV-2 spike protein in its monomeric (encompassing amino acid 1-674 for S1 and 685-1211 for S2 subunits) and trimer form (S-Trimer) formulated in the oil-in-water adjuvant system RAS-01 (Razi Adjuvant System-01). The safety and immunity of the candidate vaccine, referred to as RAZI-COV PARS were evaluated in Syrian hamster, BALB/c mice, Pirbright guinea pig, and New Zeeland white (NZW) rabbit. All vaccinated animals receiving two intramuscular (IM) and one intranasal (IN) of candidate vaccine at 3-week intervals (days 0, 21 and 51). The challenge study was performed intranasally with 5×106 pfu of SARS-CoV-2 on 35 days’ post-vaccination. None of the vaccinated mice, hamsters, guinea pigs, and rabbit showed any changes in general clinical observations, body weight and food intake, clinical indicators, hematology examination, blood chemistry and pathological examination of vital organs. Safety of vaccine after the administration of single and repeated dose was also established. Three different doses of candidate vaccine stimulated remarkable titers of neutralizing antibodies, S1, Receptor-Binding Domain (RBD) and N-terminal domain (NTD) specific IgG antibodies as well as IgA antibodies compared to placebo and control groups (P<0.01). Middle and high doses of RAZI-COV PARS vaccine significantly induced a robust and quick immune response from the 3rd-week post-immunization. Histopathological studies on vaccinated hamsters showed that the challenge with SARS-CoV-2 did not induce any modifications in the lungs. The protection of the hamster was documented by the absence of lung pathology, the decreased virus load in the lung, rapid clearance of the virus from the lung, and strong humoral and cellular immune response. These findings confirm the immunogenicity and efficacy of the RAZI-COV PARS vaccine. Of the three tested vaccine regimens, the middle dose of the vaccine showed the best protective immune parameters. This vaccine with heterologous prime-boost vaccination method can be a good candidate to control the viral infection and its spread by stimulating central and mucosal immunity.